Relevance of sex-differenced analyses in bioenergetics and nutritional studies - Garrabou, Glòria; García-García, Francesc Josep; Presmanes, Rosa Elvira; Feu, Maria; Chiva-Blanch, Gemma (Frontiers in Nutrition, 2022)
Sex-biased analyses still remain as one of the biggest limitations to obtain universal conclusions. In biomedicine, the majority of experimental analyses and a significant amount of patient-derived cohort studies exclusively included males. In nutritional and molecular medicine, sex-influence is also frequently underrated, even considering maternal-inherited organelles such as mitochondria. We herein illustrate with in-house original data examples of how sex influences mitochondrial homeostasis, review these topics and highlight the consequences of biasing scientific analyses excluding females as differentiated entities from males.